Web-based Database Courses E-Learning Application - Dela Rosa, Aaron Paul Mallari; Villanueva, Luigi Miguel; San Miguel, John Mardy; Quinto, John Emmanuel (International Journal of Computing Sciences Research, 2023)
Purpose – This study was focused on the development of a web e-learning application for the database courses taken by Information Technology (IT) students at the College of Information and Communications Technology (CICT) of Bulacan State University (BulSU). Method – The research methodology used in this project was the cross-sectional developmental approach. The Agile Software Development methodology was followed phase by phase, up to the development phase, to develop the system. It was used to produce the desired output rapidly while allowing users to go back through phases without finishing the whole cycle. Results – The goal of this study was to create a web application that teaches Structured Query Language (SQL) in both the MySQL and SQL Server approaches . The application contains quizzes and examinations to allow self-assessment of learning. Additionally, an Entity Relationship Diagram (ERD) simulation was included to provide ERD creations in a drag-and-drop fashion. This study was evaluated using ISO/IEC 25010 software quality evaluation criteria. The study's overall mean was 4.24, 4.41, and 4.33, all with the descriptive meaning of " Very Good,"  which showed that the system performed its necessary functions as perceived by students, faculty members, and experts, respectively. Conclusion – In summary, the e-learning web application for database courses was fully developed. Moreover, the entity-relationship diagram was integrated well within the system and is accessible to the users. Lastly, respondents evaluated the developed web application using the ISO/IEC 25010 with an overall descriptive interpretation of " Very Good." Recommendations – For future developments of the study, an administrator panel may be developed to manage users and do other administrative tasks. Additionally, a feature where faculty members may be included to manage contents within the application may be included. Lastly, higher-order thinking skills questions on assessments and quizzes may be included. Research Implications – The e-learning web application was fully developed and may be used as an additional teaching and learning tool upon its implementation as an e-learning web application. Faculty members may use the application as a supplemental tool in teaching the database courses. On the other hand, students may use the web application as a tool in developing entity-relationship diagrams needed for system development courses.